Qualitative research on the EFL curriculum in a school for hearing-impaired students in comparison to the chilean Ministry of Education’s guidelines. A case study - Cabello Molina, Adela Carolina (Universidad de Santiago de Chile, 2023)
Integrantes: Adela Carolina Cabello Molina, Ana María Serei Aranda, Angella Paola Vonschotter Caamaño, Yulissa Valentina Salinas Mendoza
Keywords: Inglés - Enseñanza; Sordos - Educación; Inglés - Enseñanza - Hablantes extranjeros - Metodología